Itu Upaya Peningkatan Keterampilan Proses Sains dan Keterampilan Kolaborasi dengan Penerapan Model Pembelajaran REACT pada Siswa SMA Negeri 1 Kampar Timur - Rahayu Fitri; Muhammad Nasir; Fakhruddin (Jurnal Penelitian Pendidikan IPA, 2023)
Education is an effort to improve the quality of individuals, directly or indirectly to become the basis and keep pace with the development of Science and Information Technology. Science process skills and collaboration skills are two of the few skills that can be mastered by students to keep up with the Times. However, this skill is still not fully mastered by all students. As the problem in this study is still low skills of science process and collaboration skills of Class XI students at SMAN 1 East Kampar.Â  The purpose of this study was to determine the improvement of science process skills and collaboration skills of students through the application of the REACT learning model. The method used is Class Action Research (CAR) which is carried out as many as 2 cycles. Samples in this study were students of Class XI MIPA 4. Data collection was done through collaboration skills observation sheet and science process skills test assessment. The results of this study found that there was an increase in science process skills and collaboration skills of students of Class XI MIPA 4 SMAN 1 Kampar Timur after the application of the REACT learning model.